Effectiveness and safety of the monoclonal antibody drug lecanemab (Leqembi) in reducing beta-amyloid plaques in alzheimer's dementia: a literature review - Meidina, Adinda Nezma; Ramadhanti, Nafilah; Istiqomah, Dyah Fatha; Putri, Yolanda Delia; Hasibuan, Nabila Az-zahra (Surya Hijau Manfaat, 2025)
Dementia is a syndrome characterized by cognitive decline, behavioral changes, and impaired self-care, with Alzheimer's disease (AD) being the most common cause. The global prevalence of AD is rising and is expected to reach 152 million cases by mid-century, imposing significant public health and economic burdens, particularly in low- and middle-income countries. AD is marked by synapse loss and neuronal atrophy, beginning in the hippocampus and spreading across the cerebral cortex due to β-amyloid plaque and neurofibrillary tangle accumulation, which disrupt neuronal communication and survival. Current treatments, such as memantine and cholinesterase inhibitors, provide only temporary symptom relief without stopping disease progression. Literature was searched using search engines such as Google Scholar, Science Direct, ResearchGate, and NCBI. Inclusion and exclusion criteria were applied, resulting in 27 relevant references that explored monoclonal antibody-based therapies and multidisciplinary interventions for AD management. Lecanemab has been shown to reduce amyloid accumulation effectively. However, its use is associated with risks such as amyloid-related imaging abnormalities with edema (ARIA-E) and hemorrhage ARIA-H, particularly in ApoE ε4 carriers. Despite these concerns, recent meta-analyses suggest that lecanemab is generally well-tolerated and offers potential as a cost-effective treatment for AD. Monoclonal antibody therapies, such as lecanemab, provide hope for slowing AD progression. Further research is crucial for developing more effective treatments. A multidisciplinary approach that integrates pharmacological therapies with advanced technologies may offer a more effective strategy for managing AD in the future.